Indigenous African concept of a leader as reflected in selected African novels - Tiba, Makhosini Michael (University of Limpopo (Turfloop Campus), 2012)
The mini dissertation seeks to explore the positive and negative qualities of an indigenous African leader as presented in a variety of oral texts including folktales, proverbs and praise poems as well as in the African novels of Mhudi, Maru, Things Fall Apart and Petals of Blood in order to deduce an indigenous African concept of a leader. This research is motivated by the fact that although researchers and academics worldwide acknowledge that it is very difficult to objectively define and discuss the terms ‘leader’ and ‘indigenous leader’ yet many tend to dismiss offhand such indigenous concepts of leadership as ubuntu as primitive, barbaric and irrelevant to modern institutions without examining them in detail.
Thesis (M.A. (English Studies)) --University of Limpopo, 2012
Keywords: African leaders; Folk tales; African proverbs; Praise poems; 303.34; Community leadership; indigenous peoples -- South Africa; Indigenous peoples -- Politics and government